2017
DOI: 10.1186/s40035-017-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden is increased in Parkinson’s disease with mild cognitive impairment (PD-MCI)

Abstract: BackgroundThere is limited evidence on caregiver outcomes associated with mild cognitive impairment in patients with Parkinson’s disease (PD-MCI) and the coping strategies used by these caregivers.MethodsTo investigate this relationship, we examined levels of burden, depression, anxiety, coping strategies and positive aspects of caregiving in the informal caregivers of 96 PD patients. The PD patients were classified using MDS-Task Force Level II criteria as showing either normal cognition (PD-N; n = 51), PD-MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 30 publications
4
43
0
1
Order By: Relevance
“…Similar to previous prevalent cohort studies [28][29][30][31][32][33], we found that NPS were a significant contributor to poorer quality of life in PD participants. The significance of our work is that this is evident even in newly diagnosed participants.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous prevalent cohort studies [28][29][30][31][32][33], we found that NPS were a significant contributor to poorer quality of life in PD participants. The significance of our work is that this is evident even in newly diagnosed participants.…”
Section: Discussionsupporting
confidence: 90%
“…An adequate understanding of caregiver burden necessitates that this construct can be accurately assessed. Multiple measures of caregiver burden have been developed, the most widespread and accepted is the caregiver burden inventory (CBI) (Grün et al, 2016;Hagell et al, 2017;Jones et al, 2017;Martinez-Martin et al, 2008, 2015Mosley et al, 2017;Schmotz et al, 2017;Trapp et al, 2018;Zarit et al, 1980). However, the CBI is not specific to PD; that is, many issues that might particularly affect caregivers of patients with PD are not reflected by the items of the inventory.…”
Section: Introductionmentioning
confidence: 99%
“…PwP suffer from a large variety of motor and non-motor symptoms [4,40,41]. These symptoms clearly have an impact on the HR-QoL of the patients and further on caregiver burden [2,[42][43][44][45][46][47][48]. Cognitive symptoms of PwP are correlated with a worse extent of caregiver burden [49,50].…”
Section: Discussionmentioning
confidence: 99%